2016
DOI: 10.1128/mcb.00711-15
|View full text |Cite
|
Sign up to set email alerts
|

A Repertoire of MicroRNAs Regulates Cancer Cell Starvation by Targeting Phospholipase D in a Feedback Loop That Operates Maximally in Cancer Cells

Abstract: bWe report a negative feedback loop between the signaling protein phospholipase D (PLD), phosphatidic acid (PA), and a specific set of microRNAs (miRNAs) during nutrient starvation of breast cancer cells. We show that PLD expression is increased in four breast cancer cell lines and that hypoxia, cell overcrowding, and nutrient starvation for 3 to 6 h increase expression even further. However, after prolonged (>12-h) starvation, PLD levels return to basal or lower levels. The mechanism for this is as follows. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 45 publications
0
15
0
Order By: Relevance
“…We have studied previously post-translational modification of PLD2 transcripts and reported how that is under regulation of certain miRs. 18,22 For macrophages, we selected miR-138 and miR-887 that bind to the 3'UTR of PLD2 ( Figure 5B). The demonstration that transfected miR-138 and miR-887 decrease PLD2 expression in M0 macrophages is shown in Figure 5C,D.…”
Section: Mechanism For Pld-mediated Effect Of Rvd5 In Macrophages: mentioning
confidence: 99%
See 1 more Smart Citation
“…We have studied previously post-translational modification of PLD2 transcripts and reported how that is under regulation of certain miRs. 18,22 For macrophages, we selected miR-138 and miR-887 that bind to the 3'UTR of PLD2 ( Figure 5B). The demonstration that transfected miR-138 and miR-887 decrease PLD2 expression in M0 macrophages is shown in Figure 5C,D.…”
Section: Mechanism For Pld-mediated Effect Of Rvd5 In Macrophages: mentioning
confidence: 99%
“…[15][16][17] PLD is upregulated in response to various cell stressors, such as hypoxia and nutrient starvation. 18,19 Moreover, it has been shown that PLD2 -/mice produce less pro-inflammatory cytokines in a sepsis model. 20 PA is a mitogen and a critical secondary messenger that activates many downstream pathways leading to cell growth and proliferation, vesicle trafficking and cell migration.…”
Section: Introductionmentioning
confidence: 99%
“…Increased levels of miR-887 were previously reported in endometrial and rectal cancer (77,78). In contrast, other authors have demonstrated that miR-887 may act as a tumor suppressor in prostate cancer, breast cancer and small cell lung cancer (SCLC) (79)(80)(81). We have shown that mutations in miRNA genes and known cancer driver genes are not mutually exclusive, but a substantial number of miRNA gene mutations were identified in samples without mutations in known protein-coding drivers.…”
Section: Discussionmentioning
confidence: 60%
“…There could be several reasons for this. We have studied previously post-translational modification of PLD2 transcripts and reported how that is under regulation of certain miRs (22,26). For macrophages, we selected miR-138 and miR-887 that are predicted to bind to the 3'UTR of PLD2 (Fig.…”
Section: Mechanism For Pld-mediated Effect Of Rvd5 In Macrophages: (Amentioning
confidence: 99%
“…However, the intracellular mechanism of downstream signaling in macrophages is of interest.Phospholipase D (PLD) is a ubiquitously expressed membrane-associated lipase that hydrolyzes phosphatidylcholine (PC) into free choline and phosphatidic acid (PA) (19)(20)(21). PLD is upregulated in response to various cell stressors, such as hypoxia and nutrient starvation (22,23). Moreover, PLD2 -/mice produced less pro-inflammatory cytokines in a sepsis model (24).…”
mentioning
confidence: 99%